2018
DOI: 10.1016/j.ijpddr.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic-related cell death of Trypanosoma brucei induced by bacteriocin AS-48

Abstract: The parasitic protozoan Trypanosoma brucei is the causative agent of human African trypanosomiasis (sleeping sickness) and nagana. Current drug therapies have limited efficacy, high toxicity and/or are continually hampered by the appearance of resistance. Antimicrobial peptides have recently attracted attention as potential parasiticidal compounds. Here, we explore circular bacteriocin AS-48's ability to kill clinically relevant bloodstream forms of T. brucei gambiense, T. brucei rhodesiense and T. brucei bruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…acnes , encourages us to propose it as a novel and useful candidate for its further pharmacological development against this bacterium. Available experimental data confirm that AS-48 is an amphipathic peptide characterized by a significant proportion of hydrophobic amino acid residues and rich in positively charged residues (8 lysines and 2 arginines), which selectively binds to fluid membranes with a large proportions of anionic phospholipids, as the bacterial membranes, while it leaves intact the rest of normal eukaryotic cell membranes, in which uncharged lipids predominate at the host cell surface 26 , 45 , being some trypanosomides ( Leishmania and Trypanosoma brucei ) the exception 28 , 46 . Moreover, the AS-48 selectivity for the cell membrane leads to a permeabilization that allows rapid movement of small molecules.…”
Section: Discussionmentioning
confidence: 99%
“…acnes , encourages us to propose it as a novel and useful candidate for its further pharmacological development against this bacterium. Available experimental data confirm that AS-48 is an amphipathic peptide characterized by a significant proportion of hydrophobic amino acid residues and rich in positively charged residues (8 lysines and 2 arginines), which selectively binds to fluid membranes with a large proportions of anionic phospholipids, as the bacterial membranes, while it leaves intact the rest of normal eukaryotic cell membranes, in which uncharged lipids predominate at the host cell surface 26 , 45 , being some trypanosomides ( Leishmania and Trypanosoma brucei ) the exception 28 , 46 . Moreover, the AS-48 selectivity for the cell membrane leads to a permeabilization that allows rapid movement of small molecules.…”
Section: Discussionmentioning
confidence: 99%
“…A few select bacteriocins showed some potential as antiviral agents, as plant growth promoters, and as anti-cancer agents ( Drider et al, 2016 ). Recently, it was reported that enterocin AS-48 showed promising bioactivity against the protozoan parasites of the genera Leishmania ( Abengózar et al, 2017 ) and Trypanosoma ( Martínez-García et al, 2018 ).…”
Section: Applications Challenges and Prospectsmentioning
confidence: 99%
“…In both cases, the negative surface charge of the parasites has been related to the potent effect of AS-48. Although both parasites are from the same family, different action mechanisms have been described in each one (Abengózar et al, 2017; Martínez-García et al, 2018). The activity of AS-48 against T. brucei is the highest described until now, and it is because the high efficiency in the internalization of AS-48 by the flagellar pocket of the parasite.…”
Section: Introductionmentioning
confidence: 99%